Encoding of Learned Importance of Sound by Magnitude of Representational Area in Primary Auditory Cortex - Rutkowski, Richard G.; Weinberger, Norman M.; McGaugh, James L. (Proceedings of the National Academy of Sciences - PNAS, 2005)
We hypothesized that learning-induced representational expansion in the primary auditory cortex (AI) directly encodes the degree of behavioral importance of a sound. Rats trained on an operant auditory conditioning task were variably motivated to the conditioned stimulus (CS) through different levels of water deprivation. Mean performance values correlated with deprivation level, validating them as a measure of the overall control and, therefore, behavioral importance of the CS. Electrophysiological mapping revealed expanded representations of the CS, compared with other frequencies in experimental subjects, but not in naive or visually trained controls that received noncontingent CS tones. Importantly, representational area showed a significant positive correlation with mean performance levels for only the CS band, with significant effects for relative area in contrast to only modest changes in absolute area. CS representational expansion was asymmetric into high-frequency zones, thus performance level also was significantly correlated with the relative anterior-posterior location of the enlarged representation. An increased representation of low frequencies, related to the acoustic spectrum of the reward delivery equipment, also was discovered in both experimental and control trained subjects, supporting the conclusion that behaviorally important sounds gain representational area. Furthermore, there was a surprising reduction in total AI area for the experimental and control groups, compared with untrained naive subjects, indicating that the functional dimensions of AI are not fixed. Overall, the findings support the encoding of acquired stimulus importance based on representational size in AI.